Utilization Of Electronic Technology in Ptsl Program in Karawang Regency And Its Implications On Issuance Of Electronic Documents in Land Registration Activities Based On Permen No. 3 Year 2023 - Aidina, Fitria; Guntara, Deny; Abas, Muhamad (DE LEGA LATA: JURNAL ILMU HUKUM, 2025)
The Complete Systematic Land Registration Program (PTSL) is a government strategy to provide legal certainty over land asset ownership in order to create social and economic stability in society. This legal certainty not only increases the economic value of land assets but also strengthens social harmony by minimizing the potential for agrarian conflicts. The implementation of PTSL encourages public legal awareness, creates a healthier legal environment, and facilitates transparent and legitimate land transactions. The use of technology in the implementation of PTSL however has a gap between theory and practice. This study aims to understand the use of electronic technology in the Complete Systematic Land Registration Program (PTSL) in Karawang Regency and the implications of the implementation of the Minister of ATR/BPN Regulation No. 3 of 2023 on the process of issuing electronic documents in land registration in the region. The research methodology uses qualitative analysis using an empirical legal approach, namely solving problems by examining secondary data and primary data in the field. The results of the study, in Karawang, PTSL accelerates the land legalization process and increases community participation in data collection. Collaboration between the community, technological support, and the active role of government officials are the main keys to the success of PTSL. This program is a real model of synergy between the state and society in realizing inclusive and sustainable agrarian legal certainty.